Concept of Bhakti-yoga in Indian Tradition: A Critique - Panda, N.C. (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
Bhakti yoga, is commonly known as the Path of Devotion, which teaches that the mokṣa or liberation is achieved by means of selfless and true devotion, love, and trust towards a particular deity. The Sanskrit word bhakti is derived from the root bhaj, which means “divide, share, partake, participate, to belong to”. The word also means “attachment, devotion to, fondness for, homage, faith or love, worship, piety to something as a spiritual, religious principle or means of salvation”. The term yoga literally means “union, yoke”, and in this context connotes a path or practice for “salvation, liberation”. The yoga referred to here is the “joining together, union” of one’s Ātman (true self) with the concept of Brahman (true Reality). In Indian tradition, Bhakti yoga is: “divine love mysticism, a spiritual path “synonymous for an intimate understanding of oneness and harmony of the eternal individual with the Divine (the universal Being) and all creatures, a constant delight”. Besides, Bhakti yoga, also called Bhakti mārga (literally the path of Bhakti), is a spiritual path or spiritual practice within Hinduism focused on loving devotion towards a personal God. It is one of the great paths in the spiritual practices of Hindus; others are being Jñāna yoga and Karma yoga. The benefits of Bhakti yoga are immense, as bhakti softens the heart and removes jealousy, hatred, lust, anger, egoism, pride and arrogance. It infuses joy, divine ecstasy, bliss, peace and knowledge. All cares, worries and anxieties, fears, mental torments and tribulations entirely vanish through this great path. Besides, the devotee is freed from the Sāmsaric wheel of births and deaths and he attains the immortal abode of everlasting peace, bliss and knowledge. The ultimate goal in the practice of Bhakti yoga is to reach the state of rasa (essence), a feeling of pure bliss achieved in the devotional surrender to the Divine or Supreme Lord. A number of Sanskrit texts have described Bhakti yoga in a positive way for the benefit of the devotee for obtaining liberation, which is the Highest Bliss of life. This paper aims at highlighting the nature and characteristics of Bhakti yoga as rightly focussed in Indian tradition.